The Imagery Types Analysis Of "Verses Upon The Burning Of Our House" Poetry Intrinsic Elements By Anne Bradstreet - Agustina, Kezia; Laksminy, Luh Putu (International Journal of Linguistics and Discourse Analytics, 2024)
In Literature, Poetry is one of various literary works that usually can become a medium to express the expression, emotions, thoughts, imaginations, visions, and whatever the poet feels. By using poems as a form of feeling expression, famous poets often add supporting elements of poetry in order to give an element of beauty to each line of poetry that makes semantic meaning and includes rhymes and rhythms. One of the many famous poets who can expresses her feelings and thoughts into a poem is Anne Bradstreet, one of the earliest American poets. One of Anne Bradstreet's poems inspired by her thoughts, visions and feelings is her poem entitled "Verses Upon the Burning of our House". The poem has choose between the others to be analyzed because it was consist of her real-life experience that she has pass trough when alive. This research aims to find out the intrinsic element especially in imagery context that contain the poem titled “Verses Upon the Burning of our House” by Anne Bradstreet. The poem is about the experience of Anne Bradstreet losing her house into a flames on July 10, 1666 and describes the emotional impact of watching her material possessions, including her house, go up in flames. This research is used library research because researchers need data from various sources such as undergraduate thesis, articles, books, and internet sources in order to obtain a theoretical basis regarding the problem to be researched also descriptive qualitative method with Kennedy (1995) intrinsic elements concept as the theory to describe all the elements that found in the poem. As the result, from 7 types of imagery that exist there are 4 types found in the poem that consist 8 stanza with 54 lines. They are visual with the most type that appear with 17 lines, auditory with 8 lines, kinesthetic with 8 lines, organic with 9 lines and the other 12 lines without any imagery classification types